2002
DOI: 10.1111/1467-9507.00183
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Gender Difference in False Belief Development?

Abstract: The contribution of children's social environment to their acquisition of theory of mind skills, combined with the well documented advantage for girls in mental state talk with siblings, peers and mothers, might lead to a female advantage on false belief tasks. We present a post-hoc analysis of large datasets from two independent laboratories. A slight advantage for girls on false belief task performance was found in both datasets and was only apparent in younger but not older children. Language ability could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
3
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 51 publications
15
104
3
8
Order By: Relevance
“…In terms more specific to theory of mind, similar sex differences have been found in the ability of adults to mindread (BaronCohen & Hammer, 1997). Female superiority has also been found with children in such areas as predicting and explaining false beliefs (Cutting & Dunn, 1999), assessing the motives and feelings of characters in a story (Bosacki & Astington, 1999), distinguishing between the appearance and reality of emotion (Banerjee, 1997), and false belief development (Charman, Ruffman, & Clements, 2002). One study has even identified a female preference for social stimuli just 24 hours after birth (Connellan, Baron-Cohen, Wheelwright, Ba'tki, & Ahluwalia, 2001).…”
Section: The Extreme Male Brain Theorymentioning
confidence: 99%
“…In terms more specific to theory of mind, similar sex differences have been found in the ability of adults to mindread (BaronCohen & Hammer, 1997). Female superiority has also been found with children in such areas as predicting and explaining false beliefs (Cutting & Dunn, 1999), assessing the motives and feelings of characters in a story (Bosacki & Astington, 1999), distinguishing between the appearance and reality of emotion (Banerjee, 1997), and false belief development (Charman, Ruffman, & Clements, 2002). One study has even identified a female preference for social stimuli just 24 hours after birth (Connellan, Baron-Cohen, Wheelwright, Ba'tki, & Ahluwalia, 2001).…”
Section: The Extreme Male Brain Theorymentioning
confidence: 99%
“…The young participants were aged between 19 and 25 years (mean age = 22; 4 females and 26 males). The gender proportions of the two age groups were matched because females tend to perform better on theory of mind tasks (Bosacki, 2000;Charman, Ruffman, & Clements, 2002;Walker, 2005). All participants were healthy.…”
Section: Participantsmentioning
confidence: 99%
“…It is found that school readiness may be enhanced by having a theory of mind and that theory of mind development is further enhanced by schooling (Homer & Tamis-LeMonda, 2005). Astington and Pelletier (2005) suggest that child's capacity to mentalize allow him to understand the need and process of learning. Also, this skill may affect the socio-emotional domain, which also has it's own impact on later academic learning.…”
Section: Responsibility Of the Conference Organization Committeementioning
confidence: 99%
“…Children with more developed theory of mind are more socially competent, they are better in communication and in resolving conflicts with peers, as well as they are more popular with friends (Dunn, 1996). On the other side, in the cognitive domain, their teachers rate them as and their school work is more advanced in some ways (Astington & Pelletier, 2005).…”
Section: Responsibility Of the Conference Organization Committeementioning
confidence: 99%